KUALITAS PELAYANAN AKTA KELAHIRAN PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN BANGGAI - Kawulo, Noto; Setiawati, Budi; Wardah, Wardah (Universitas Muhammadiyah Makassar, 2024)
The aim of this research is to find out the quality of services for making birth certificates at the Population and Civil Registration Service of Banggai Regency. The type used in this research is phenomenology where the researcher collects data by distributing questionnaires and observations. The type of research used in this research is quantitative descriptive research to find out or describe the reality of the events being studied or the research being carried out. Where the results of the research show that the quality of services for making birth certificates at the Population and Civil Registration Service of Banggai Regency received a score of 4.22 with a percentage of 84.23%, so it can be said that the quality of services for making birth certificates at the Population and Civil Registration Service of Banggai Regency is very high quality. With this, it is important to maintain the quality of service that has been achieved and further improve it by continuing to innovate in providing services to the community.